(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
expenses which will converge with the interests, possibilities and needs of the largest number of the Alliance member-states especially with the Republic of Macedonia as an aspirant for Alliance membership. This is done on the basis of analysis of research material for dimensions and armed forces of the Alliance member states. Our starting point was the understanding that significant changes in dimension of the armed forces take place in a period of deep sociopolitical, economic and defense changes, as in the case after the end of the Cold War. Another starting point was that in conditions of deep social and other changes, when it estimated that the endangering of the states’ security is on lower level than before, then most frequently happens not only decrease of the armed force, but also decrease of the defense budget. The most serious test for justification of those decisions is the engagement in the regions in crisis, when the needs for additional expenses and continuous engagement of armed forces with increases capabilities are most directly exposed.